Evaluation of Usability on Bionic Anthropomorphic (BIMO) Hand for Disability Hand Patient - Novie Susanto; Heru Prastawa; Manik Mahachandra; Dinda Ayu Rakhmawati (Jurnal Ilmiah Teknik Industri, 2019)
One aspect that needs to be assessed to make better product is usability.  Testing the level of usability on BIMO hand is performed using adapted Southampton Hand Assesment Procedure (SHAP) method. Users are given the task of using prosthetic hand to perform daily activities according to performance measurement rules. Based on the opinion of Jacob Nielsen, the theory used to measure usability are 5 main parameters, i.e: Learnability, Memorability, Efficiency, Satisfaction, and Errors. Testing is done by giving 15 task daily activity to the respondent. After testing, respondents were given USE questionnaires (Usefulness, Satisfaction and Ease of use) as a media for usability assessmentand received suggestions from respondents. Some suggestions were obtained from the respondents after the research was conducted, such as the size of the product, censoric product respond, the suitability shape and weight of product. Based on the percentage of USE questionnaire assessment known Usability Prosthetic hand level tested is in the status of GOOD, this indicates the respondents feel the product is good to use.